The Concept of an Infrastructure Location to Supply Buses with Hydrogen: A Case Study of the West Pomeranian Voivodeship in Poland - Ludmiła Filina-Dawidowicz; Dawid Miłek; Dalia Baziukė (Energies, 2025)
The growing energy crisis and increasing threat of climate change are driving the need to take action regarding the use of alternative fuels in transport, including public transport. Hydrogen is undoubtedly a fuel which is environmentally friendly and constitutes an alternative to fossil fuels. The wider deployment of hydrogen-powered vehicles involves the need to adapt infrastructure to support the operation of these vehicles. Such infrastructure includes refuelling stations for hydrogen-powered vehicles. The widespread use of hydrogen-powered vehicles is dependent on the development of a network of hydrogen refuelling stations. The aim of this article is to propose the conceptual location of infrastructure for fuelling public transport vehicles with hydrogen in selected cities of the West Pomeranian Voivodeship, in particular the cities of Szczecin and Koszalin. The methodology used to determine the number of refuelling stations is described, and the concept of the location for the refuelling stations has been proposed. Based on a set assumptions, it was stated that two stations may be located in the Voivodeship in 2025 and seven stations in 2040. The research results will be of interest to infrastructure developers, public transport companies, and municipalities involved in making decisions related to the purchase and operation of hydrogen-powered buses.